Social Justice in Friedrich Hayek’s Thought - Gappo, Patrick Coelho Campos (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
We discuss the question of social justice in Friedrich Hayek’s thought, beginning with a panorama of liberal thought, trying to show how the author inserts in it. Afterwards, we present the main concepts of Hayek’s political philosophy and finally we use this basis to discuss how he denies the concept of social justice. We conclude with some reflections about the subjects discussed and the issue of market order.